The Sexual Risk Behaviors Scale (SRBS): Development & Validation in a University Student Sample in the UK. Issue 2 (June 2021) - Fino, Emanuele; Jaspal, Rusi; Lopes, Bárbara; Wignall, Liam; Bloxsom, Claire
University students are at risk of poor sexual health outcomes. The aim of this study was to develop and test the psychometric properties of the Sexual Risk Behaviors Scale (SRBS), a novel short tool for measuring engagement in sexual risk behaviors in university students. We developed a pool of six items based on a review of recent literature and tested its properties in 547 undergraduate students in the United Kingdom. We used Exploratory Factor Analysis and Confirmatory Factor Analysis to explore and determine the factor structure and dimensionality of the SRBS. We used Item Response Theory and specifically the Graded Response Model to investigate items' discrimination, information, and differential functioning, respectively, and logistic regression to test whether higher SRBS scores predicted a diagnosis of any sexually transmitted infections in the past 12 months. Results showed that a unidimensional, five-item model fitted the data well, showing satisfactory fit indices and reliability, with all items providing adequate discrimination and information, and no differential item functioning by gender nor by sexual orientation. SRBS total scores significantly predicted the odds of being diagnosed with sexually transmitted infections in the past 12 months. Implications for public health prevention and intervention are discussed.